Africentric-Career Counselling Strategies and the Enhancement of Employability Soft Skills In Persons with Disabilities in Buea Municipality - Fangwi, Melem Linda (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This study investigates the impact of two Africentric career counselling strategies; cultural story telling and mentor-discussion techniques on the enhancement of employability soft skills in persons with disabilities in Buea Municipality. Employability soft skills such as communication, time management, interpersonal skills, planning and resource management skills and adaptability and flexibility are essential for workforce participation and career success yet persons with disabilities in Cameroon often struggle to develop these skills. Through a mixed method approach, a sample of 25 persons (employees) with disabilities and 5 counsellors and 5 employers in Buea municipality were purposively selected as participants in the study. Specifically, an embedded design was utilized to address the various research questions. Quantitative data were collected followed by a qualitative intervention, where a structured employability training program was organized and implemented by the researcher. Semi-structured interviews were then conducted to gather qualitative data from the participants and their employers. The findings revealed that both cultural story-telling and mentor-discussion techniques boost the following employability soft skills in persons with disabilities, communication, time management, interpersonal skills, planning and resource management skills and adaptability and flexibility. The study emphasized the importance of tailoring career counselling services to local contexts to address the unique needs and challenges faced by persons with disabilities in the workforce. It concludes that Africentric strategies do not only enhanced employability soft skills but also promote greater social inclusion and economic participation for persons with disabilities.